On effective acceleration of charged particles in vacuum - Buts, V.A.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2021)
The results of studying the dynamics of particles in the fields of large-amplitude transverse electromagnetic waves are presented. The main attention is paid to the description of the found conditions, under which the effective transfer of wave energy to charged particles in vacuum is possible. Викладено результати дослідження динаміки частинок у полях поперечних електромагнітних хвиль великої потужності. Основна увага звернена на опис виявлених умов, при виконанні яких можлива ефективна передача енергії хвилі до заряджених частинок у вакуумі. Изложены результаты исследования динамики частиц в полях поперечных электромагнитных волн большой амплитуды. Основное внимание обращено на описание обнаруженных условий, при выполнении которых возможна эффективная передача энергии волны заряженным частицам в вакууме.